1992
DOI: 10.1007/bf01289817
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of209Bi and238U photofission cross section in the quasi-deuteron region of photonuclear absorption

Abstract: Abstract. An analysis of the photofission reactions in the quasi-deuteron energy range of photonuclear absorption (~30-140 MeV) has been performed for 2~ and 238U nuclei. Experimental cross section data available in the literature have been compared with calculated values obtained from a model in which the incoming photon is assumed to be absorbed by a neutron-proton pair (Levinger's quasi-deuteron photoabsorption), followed by a mechanism of evaporation-fission competition for the excited residual nuclei. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 43 publications
3
38
0
1
Order By: Relevance
“…A fourth possibility there exists clearly of obtaining residual nuclei, namely, escaping of both the neutron and proton simultaneously from the nucleus. In this case, however, no excitation energy is left to the residual nucleus, with the consequence of null chance for fission from this residual [14]. Let τ n and τ p denote, respectively, the probabilities of escaping for neutron and proton from the nucleus (without suffering for any secondary interaction), i.e., the nuclear transparencies to neutron (τ n ) and proton (τ p ).…”
Section: Nuclear Excitation and Fission Probabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…A fourth possibility there exists clearly of obtaining residual nuclei, namely, escaping of both the neutron and proton simultaneously from the nucleus. In this case, however, no excitation energy is left to the residual nucleus, with the consequence of null chance for fission from this residual [14]. Let τ n and τ p denote, respectively, the probabilities of escaping for neutron and proton from the nucleus (without suffering for any secondary interaction), i.e., the nuclear transparencies to neutron (τ n ) and proton (τ p ).…”
Section: Nuclear Excitation and Fission Probabilitymentioning
confidence: 99%
“…Nuclear transparencies depend essentially upon neutron and proton kinetic energies in their final states [12,14]. For photons in the energy range 60-130 MeV interacting with actinides, it is found that for almost ∼ 80% of cases excited residual nuclei are formed (E * 1 ≈ E * 2 ≈ E γ /2, hence, highly fissionable residuals), and the third mode of formation is the predominant one.…”
Section: Nuclear Excitation and Fission Probabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The routine calculation of the probability-values for the neutron emission (n), proton emission (p), alpha-particle emission (α), and fission (f ) modes has been already detailed in [5][6][7]. For the level-density parameter of the residual nucleus after neutron evaporation, a n , we adopted the expression…”
mentioning
confidence: 99%